A continuous 4000-year lake-level record of Owens Lake, south-central Sierra Nevada, California, USA. Issue 2 (2nd July 2018) - Bacon, Steven N.; Lancaster, Nicholas; Stine, Scott; Rhodes, Edward J.; McCarley Holder, Grace A.
Abstract: Reconstruction of lake-level fluctuations from landform and outcrop evidence typically involves characterizing periods with relative high stands. We developed a new approach to provide water-level estimates in the absence of shoreline evidence for Owens Lake in eastern California by integrating landform, outcrop, and existing lake-core data with wind-wave and sediment entrainment modeling of lake-core sedimentology. We also refined the late Holocene lake-level history of Owens Lake by dating four previously undated shoreline features above the water level (1096.4 m) in AD 1872. The new ages coincide with wetter and cooler climate during the Neopluvial (~3.6 ka), Medieval Pluvial (~0.8 ka), and Little Ice Age (~0.35 ka). Dates from stumps below 1096 m also indicate two periods of low stands at ~0.89 and 0.67 ka during the Medieval Climatic Anomaly. The timing of modeled water levels associated with 22 mud and sand units in lake cores agree well with shoreline records of Owens Lake and nearby Mono Lake, as well as with proxy evidence for relatively wet and dry periods from tree-ring and glacial records within the watershed. Our integrated analysis provides a continuous 4000-yr lake-level record showing the timing, duration, and magnitude of hydroclimate variability along the south-central Sierra Nevada.